Access to HIV care in jails: Perspectives from people living with HIV in North Carolina - Blue, Colleen; Buchbinder, Mara; Brown, Mersedes E.; Bradley-Bull, Steve; Rosen, David L. (PLOS ONE, 2022)
Most incarcerations for people living with HIV (PLWH) occur in jails, yet studies of HIV care during jail incarceration are limited. As part of a larger study to explore the ethical considerations in extending public health HIV surveillance to jail settings, we conducted semi-structured interviews with twenty-three PLWH with more than 300 distinct jail incarcerations post HIV diagnosis in 21 unique North Carolina jails. Interviews included questions about HIV disclosure in jail, the type of HIV care received in jail, and overall experiences with HIV care in jail. We report on participants’ experiences and perspectives in four domains: access to HIV care in jail; impact of jail incarceration on continuity of HIV care; privacy and stigma; and satisfaction with HIV care in jail. Although most participants received HIV medications and saw providers while in jail, almost half reported that their greatest challenge in regard to HIV care was obtaining their HIV medications in the face of limited jail resources or policies that made access to medications difficult. Findings from this study suggest that jail leadership should review internal policies regarding HIV medications to ensure that PLWH can receive them quickly upon entry into jail. Findings also suggest that more external resources are needed, for example from state and local health departments, so that jails can provide timely HIV medications for PLWH incarcerated in their facilities.